2005
DOI: 10.1177/08857288050280010601
|View full text |Cite
|
Sign up to set email alerts
|

Transition to Adult Roles for Students With Emotional/Behavioral Disturbances

Abstract: Transition from adolescence to adulthood is especially challenging for youth and young adults with emotional/behavioral disturbances (EBD). The Transition to Independence Process (TIP) model serves to prepare and facilitate youth and young adults with EBD in their transition into adulthood roles through a person-centered and developmentally appropriate process. Using existing state and program data, this study compared the postsecondary outcomes (e.g., employment, postsecondary education, incarceration) of exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 22 publications
2
37
0
1
Order By: Relevance
“…Research has shown that a previous paid or unpaid work experience is a significant predictor of job retention (Colley & Jamison, 1998;Fabian, et al, 1998;Karpur, et al, 2005). Level of education, income, health, and perceptions of disability also had a significant impact on job retention in several studies (Colley & Jamison, 1998;Fabian, et al, 1998;Hasnain & Balcazar, 2009).…”
Section: Among Many Others)mentioning
confidence: 98%
See 2 more Smart Citations
“…Research has shown that a previous paid or unpaid work experience is a significant predictor of job retention (Colley & Jamison, 1998;Fabian, et al, 1998;Karpur, et al, 2005). Level of education, income, health, and perceptions of disability also had a significant impact on job retention in several studies (Colley & Jamison, 1998;Fabian, et al, 1998;Hasnain & Balcazar, 2009).…”
Section: Among Many Others)mentioning
confidence: 98%
“…According to several studies, being either Asian or White, and male is associated with securing a job during and after school exit Entwisle, et al, 2000;Fabian, 2007;Hasnain & Balcazar, 2009;Wagner, et al, 2005). Other significant factors include having prior work experience (Colley & Jamison, 1998;Fabian, 2007;Wagner, et al, 2005), having participated in vocational education (Karpur, Clark, Caproni, & Sterner, 2005), and having a career goal (Benz, Lindstrom, & Yovanoff, 2000). In addition, age, sex, stability of home environment, receiving Supplemental Security Income (SSI), staying in high school, and having an employed sibling also affect whether or not youths with disabilities secure a job during their transition from high school (Fabian, 2007;Fabian, Lent, & Willis, 1998;Gardecki, 2001;Wagner, et al, 2005).…”
Section: Among Many Others)mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, socioeconomic disadvantage and poor literacy histories are major descriptors of youth who are disaffected, cease schooling early and fail to transition successfully into employment [4]. Typically, there are negative and enduring consequences for youth with such background, in their personal adjustment and relational futures [8], [18], [28], [29] with high rates of social offendingusually with associated arrests and incarceration [10], [11], [55] and connected disadvantage to national wellbeing and economic strength. Thus, designing effective intervention to motivate disadvantaged students to read, to persist as readers, to read more and to improve their reading performance, is urgently required [1] & [46].…”
Section: Introductionmentioning
confidence: 99%
“…These students consistently demonstrate ongoing academic, behavioral, and social deficits in schools that continuously challenge educators (Walker, Ramsey, & Gresham, 2004). Specifically, many students with emotional and behavioral disorders (EBD) experience school truancy, poor social skills, low self-regulation, school dropout, school violence, and eventually, incarceration, unemployment, or underemployment (Karpur, Clark, Caproni, & Sterner, 2005;Sinclair, Christenson, & Thurlow, 2005). As a result of these challenges, teachers are consistently confronted with student internal and external behaviors in the classroom.…”
mentioning
confidence: 99%